Clean Environment as a Human Right: A Global Concern (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Right to clean and healthy environment is one of the essential ingredients for human existence. Speedy scientific and industrial development has polluted the environment to such an extent that the survival of human existence on earth is in danger. Taking pollution as a big threat for human existence, the international community has been trying to combat the same. The United Nations has always been a strong supporter of clean and healthy environment. The General Assembly on Decembers, 1968 passed a resolution calling upon the member states to pay attention to the problems of environment. The Stockholm Conference on Human environment developed the concept of Environmental Jurisprudence. The Earth Summit organised by United Nation at Rio de Janario in June 1992 sets out specific programmes to put an end to ecological destruction. India being a member of the United Nations, has made elaborate provisions in its Constitution and in other laws to protect and preserve the environment. Article 21 of the Constitution includes clean and healthy environment as an essential ingredient of right to life. Some specific laws have been made to deal with environment. The Indian judiciary has also been in favour of pollution free environment. It has issued various guidelines for better environment protection.